Pulmonary tuberculosis in health care workers in Dos de Mayo National Hospital, Lima - Contreras, Carlos (2019)
OBJECTIVE. Determine the epidemiological profile of health care workers (HCW) affected by pulmonary tuberculosis (PT) in Dos de Mayo National Hospital (DMNH), Lima, Peru. MATERIAL AND METHODS. An observational, descriptive and retrospective study. The population were HCW diagnosed with PT in Dos de Mayo National Hospital. Epidemiological variables were collected: Age, gender, comorbidity, occupational group, service or department they belong, working situation, time of service, among others. For quantitative variables the mean, standard deviation, range and lower and upper value were determined, for qualitative variables the frequency analysis like absolute and relative frequencies were used. Incidence rates for 100 000 was determined and statistical tests of central tendency and dispersion were used; p value < 0,05 was considered as significant. RESULTS. The usual incidence rate of PT was 348 per 100 000. The most affected group was the auxiliary technical staff (23,96 %). The average age was 35,52 year-old ( ± 10,22) and 70,83 % were under of 40 year-old. The average time of hospital work was 9,23 years (± 7,32); 91,70 % had service time ≤ 20 years; 66,67 % belonged to the departments of Medicine and Emergency; 72,92 % of the affected HCW, were from the clinical areas; 11,45 % of surgical areas and 3,13 % belonged to auxiliary and diagnostic support services. CONCLUSIONS. The usual rate of PT of HCW in the HNDM was approximately 4,22 times higher than the national incidence rate. The most affected HCW were auxiliary technical staff, appointed workers, age under of 40 years old, with service time under 20 years, health care workers that work in clinical areas and more than 60 % belonged to the medicine and emergency departments.